Zammara smaragdula walker, 1858 (hemiptera: Cicadidae): First record for Brazil - Maccagnan, Douglas Henrique Bottura; Martinelli, Nilza Maria [UNESP]; Goemans, Geert; Guilherme, Edson (My University, 2011)
The present note reports the first record for Brazil of the cicada Zammara smaragdula Walker, 1858 (Hemiptera, Cicadidae, Zammarini). This new record brings the number of reported Cicadidae species for Brazil to 153, including three species in the genus Zammara. © 2011 Check List and Authors.
Keywords: Cicada; Cicadidae; Hemiptera; Zammara